Imperfect detection distorts depth‐related trends in marine macrofaunal species richness. Issue 10 (23rd February 2018) - Karenyi, Natasha; Sink, Kerry; Nel, Ronel; Clark, Allan E.; Altwegg, Res
Abstract : Ecology and biodiversity research are underpinned by species richness patterns and their environmental drivers. However, a key topic in this discussion is the accuracy of these patterns which are greatly dependent on species detection probabilities. Due to variations in detection of species, true ecological patterns may be distorted. This is particularly true for subtidal macro‐infaunal communities. We tested three hypothesized relationships between marine benthic macrofaunal diversity and depth using species richness per site estimated with a capture–recapture heterogeneity model that accounts for variable detection probabilities. These metrics were based on data from 42 replicated sites across the continental shelf of the Southern Benguela. Average detection probability decreased with greater depth but species richness increased along the same depth gradient. The conflation of these trends in observed diversity data resulted in a positively near‐linear depth–diversity relationship, while accounting for variable species detection revealed a much stronger relationship. Ignoring species detection in ecosystems with imperfect detection could therefore distort species richness patterns, which has implications for ecological theory, management and conservation.